Digital finance and welfare in Sub-Saharan Africa - Mphefo, Lebogang (Graduate School of Business (GSB), 2024)
This research investigates the reliability of measuring the effect of financial inclusion on welfare in Sub-Saharan Africa (SSA) using the traditional financial inclusion index, which encompasses traditional access to financial services but does not necessarily represent the marginalised, as the majority do not make use of formal financial services. It is from this narrative that the study derives three financial inclusion indices – traditional financial inclusion, digital financial inclusion and comprehensive financial inclusion – using the three-stage PCA methodology to establish the influence of financial inclusion on welfare, and to add to the debate on the appropriate approach to measuring financial inclusion in the region. The traditional financial inclusion index is derived from traditional banking variables (the ATM and the branch), while the digital financial inclusion index employs mobile banking variables and the comprehensive financial inclusion index is a combination of digital and traditional financial inclusion indices used to compute the overall financial inclusion index. Welfare is proxied by the human development index and an inequality-adjusted human development index to establish the effect of inequality on welfare and financial inclusion. The fixed-effect regressions were conducted on a panel of 41 sub-Saharan countries for the years 2011, 2014 and 2017, to explore the relationship between traditional financial inclusion and welfare, while the pooled OLS methodology was adopted to enable multi-regression of digital financial inclusion, comprehensive financial inclusion and welfare in 2017, due to mobile data limitations on the demand side. Unemployment and bank credit ratio were included in the models to support the rationalisation of the results in alignment with the literature. The empirical findings indicate that digital financial inclusion and education are the main factors for improving welfare, and not necessarily national income – which was the case previously in the financial development era – because the digital financial inclusion index is the most optimal approach to calculating financial inclusion in SSA. On average, the traditional financial inclusion index is lagging, while the comprehensive inclusion index mirrors the movement of the digital financial inclusion index, and therefore reflects the dominance of digital inclusion in the region. However, overall financial inclusion (represented by comprehensive financial inclusion) is insignificant to welfare; implying that financial inclusion is low and the depth of financial services available on digital platforms is not at a level of significance to impact welfare immensely. Inequality-adjusted welfare has a significant and positive relationship with traditional and digital financial inclusion when regressed with education, but not with income. This implies 4 that with education, inequality can be overcome through financial inclusion to yield improved welfare. This study also shows the use of mobile banking to be higher in medium to large-sized informal economies. Lastly, unemployment is significant and positively related to welfare through digital financial inclusion and education, due to opportunities created in the informal sector.